2022
DOI: 10.3390/ma15176128
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of CaO and MgO on the Mechanical Properties of Alkali-Activated Blast Furnace Slag Powder

Abstract: CaO and MgO are both reported as effective activators for blast furnace slag. However, the synergistic effect of these two components on the mechanical properties of alkali-activated blast furnace slag remains unclear. In this study, the flexural and compressive strengths of alkali-activated blast furnace slag powder with MgO and CaO range from 0% to 30% by the mass ratio of alkali-activated blast furnace slag powder are investigated. Moreover, the dry shrinkage rate of alkali-activated blast furnace slag powd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 41 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…In addition, as illustrated in Figure 8, the second step can be observed, which is the temperature of 368.2 °C. In this step, the TG values decrease, which is ascribed to the decomposition of calcium silicate hydrate, the hydrated single sulfur calcium sulphoaluminate and hydrated polysulfur calcium sulphoaluminate [20,36]. As illustrated in Figure 8, the TG values are decreased by CO2 curing, due to the fact that CO2-cured alkali-activated compound mineral admixtures show less bound water than the alkali-activated compound mineral with standard curing, thus decreasing the reduction of TG values.…”
Section: The Mechanical Strengthsmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, as illustrated in Figure 8, the second step can be observed, which is the temperature of 368.2 °C. In this step, the TG values decrease, which is ascribed to the decomposition of calcium silicate hydrate, the hydrated single sulfur calcium sulphoaluminate and hydrated polysulfur calcium sulphoaluminate [20,36]. As illustrated in Figure 8, the TG values are decreased by CO2 curing, due to the fact that CO2-cured alkali-activated compound mineral admixtures show less bound water than the alkali-activated compound mineral with standard curing, thus decreasing the reduction of TG values.…”
Section: The Mechanical Strengthsmentioning
confidence: 96%
“…Additionally, the compressive strengths of alkaliactivated BFS and FA can reach values higher than 80 MPa and 100 MPa, respectively. Feng et al found that the assembly unit of CaO and MgO can improve the mechanical strengths, high temperature resistance and compactness of the microstructure [20]. The compressive strength of ordinary concrete is less than 60 MPa while high performance concrete shows a compressive strength of 60 MPa-100 MPa; therefore, the compressive strength of alkali-activated BFS is close to the compressive strength of ultra-high performance concrete.…”
Section: Introductionmentioning
confidence: 99%
“…The material combinations required per cubic meter of AASCMS are shown in Table 3. Previous studies had shown [18] that AASCM exhibits good performance when the modulus of potassium silicate is 1.0, the alkali content is 14% and the fiber content is 1% by mass. Thus, the fiber content in this study adopted 1% for all testing samples.…”
Section: Ratio Designmentioning
confidence: 99%
“…Ground-granulated blast-furnace slag (GGBS) is a kind of high-activity waste slag formed via the quenching and granulation of silicate and alumino-silicate as the main components in blast-furnace smelting pig iron. Feng et al [ 5 ] prepared an alkali-activated GGBS material with CaO and MgO as activators. It was reported that the addition of MgO and CaO helps to improve the mechanical strengths of alkali-activated GGBS.…”
mentioning
confidence: 99%